Persepsi Konsumen Terhadap Faktor-Faktor Yang Mempengaruhi Perilaku Berbelanja Di Ayani Mega Mall Pontianak - Fitri Kurniati (JURNAL MANAJEMEN MOTIVASI, 2015)
This study aims to determine consumer perceptions of the factors that influence the decision of consumers shopping at Mega Mall Ayani Pontianak. This research uses descriptive method through a qualitative approach. The population in this study is that consumers who visit and shop at Mega Mall Ayani Pontianak. Samples taken as many as 100 respondents using accidental sampling technique. Data were analyzed using analysis of the average score (mean) then the results are interpreted and drawn kesimpulan.Hasil research shows that consumers' perceptions of the factors that influence the decision of consumers shopping at Mega Mall Ayani Pontianak included either. This is due to the availability of a wide range of consumer needs while providing a variety of entertainment options. Social factors include the reference group, the family and the role and status affect consumer decisions Ayani Mega Mall shopping in Pontianak, where the family plays a major role against the decision of consumers shopping at the mall followed by the reference group and the role and social status.